STUDENTS’ PERCEPTION ON ONLINE GAME MOBILE LEGENDS FOR VOCABULARY DEVELOPMENT - Adil Dananjaya; Dyah Kusumastuti (Universitas Muhammadiyah Jember, 2019)
The purpose of this research is to discover the level of EFL students’ perception of online game Mobile Legends in their vocabulary development. The researcher used questionnaire and interview as the instrument to collect the data and took 20 respondents for the questionnaire and 5 interviewees that are taken from 8th semester students of English Education Department on 2018/2019 academic year in Universitas Muhammadiyah Purwokerto. This study got a positive result with 74%, therefore can be categorized as positive perception. Moreover, it was supported by the interview result where the interviewees agreed that their vocabulary knowledge is expanding when playing Mobile Legends.